Does lateral banking and radius affect well-trained sprinters and team-sports players during bend sprinting? - White, J.; Wilson, C.; von Lieres Und Wilkau, H.; Wyatt, H.; Weir, G.; Hamill, J.; Irwin, G.; Exell, T. A. (Journal of Sports Sciences, 2023)
This study investigated the short-term responses of step characteristics in sprinters and team-sports players under different bend conditions. Eight participants from each group completed 80 m sprints in four conditions: banked and flat, in lanes two and four (L2B, L4B, L2F, L4F). Groups showed similar changes in step velocity (SV) across conditions and limbs. However, sprinters produced significantly shorter ground contact times (GCT) than team sports players in L2B and L4B for both left (0.123 s vs 0.145 s and 0.123 s vs 0.140 s) and right steps (0.115 s vs 0.136 s and 0.120 s vs 0.141 s) (p > 0.001-0.029; ES = 1.15-1.37). Across both groups, SV was generally lower in flat conditions compared to banked (Left: 7.21 m/s vs 6.82 m/s and Right: 7.31 m/s vs 7.09 m/s in lane two), occurring due to reduced step length (SL) rather than step frequency (SF), suggesting that banking improves SV via increased SL. Sprinters produced significantly shorter GCT in banked conditions that led to non-significant increases in SF and SV, highlighting the importance of bend sprinting specific conditioning and training environments representative of indoor competition for sprint athletes.